Assessment of Development in Preschool Children Aged 60-72 Months Using the KPSP (Pre-Screening Development Questionnaire) at Sawitto Kindergarten, Pinrang Regency - Muhammad Saleng; Syarifuddin Syarifuddin; Edi Hasan; Sri Husna Yusuf (LPPM STIKes Muhammadiyah Ciamis, 2025)
Sustainable Development Goals (SDGs) must begin with the development of children. Monitoring children's growth and development is very important. The role of parents in family life can determine the steps that must be taken to help children's development. Early detection of child development is carried out through periodic developmental assessments in four areas, namely gross motor skills, fine motor skills, language and cognitive skills, independence, and socialization. The purpose of this study was to determine the description of the assessment of children aged 60-72 months using the Developmental Pre-Screening Questionnaire (KPSP) at Sawitto Kindergarten in Pinrang Regency. This study used a descriptive method with a total sampling technique involving 35 children. Based on the data obtained, the majority of children aged 60-72 months were in the category of development appropriate for their age, namely 28 children (80%), 5 children (14.3%) were in the doubtful category, and 2 children (5.7%) were in the developmental deviation category. Children aged 72 months tended to show better development than children aged 60 months, indicating that as they get older, children generally experience better developmental improvement. In addition, the development of boys was slightly more dominant than that of girls. Of the four aspects of development analyzed, gross motor skills showed the most optimal results, while speech and language were the aspects that experienced the most discrepancies. This study recommends improving periodic monitoring of child development through instruments such as the KPSP, in order to detect developmental delays or deviations at an earlier stage.